2020
DOI: 10.3390/molecules25194531
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Imidazopyridine Nucleoside Derivatives Designed as Maribavir Analogues

Abstract: The strong inhibition of Human Cytomegalovirus (HCMV) replication by benzimidazole nucleosides, like Triciribine and Maribavir, has prompted us to expand the structure–activity relationships of the benzimidazole series, using as a central core the imidazo[4,5-b]pyridine scaffold. We have thus synthesized a number of novel amino substituted imidazopyridine nucleoside derivatives, which can be considered as 4-(or 7)-aza-d-isosters of Maribavir and have evaluated their potential antiviral activity. The target com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The tested compounds belong to our in-house compounds library and were aromatic nitrogen heterocycles with originally purposed for antiproliferative activity, 37,46,47 against angiogenesis, 48 as fluorescence tracers in cells, 49 against hepatitis B virus, 50 and nucleosides originally tested against adenosine deaminase, 51 hepatitis C virus, 52 and human cytomegalovirus. 53 We found that pyrazolo [3,4-c]pyridine, is a novel heterocyclic ring that bind ARs having antagonistic activity to A1R and A3R with potential for further development. We investigated experimentally for the identified two classes of pyrazolo [3,4-c]pyridines their (a) pharmacological profile using functional assays, (b) binding interactions and binding kinetic profile using, correspondingly, molecular dynamics (MD) simulations and mutagenesis experiments, and competition binding experiments with the NanoBRET 20 (Nano Bioluminescence resonance energy transfer) method.…”
Section: Introductionmentioning
confidence: 99%
“…The tested compounds belong to our in-house compounds library and were aromatic nitrogen heterocycles with originally purposed for antiproliferative activity, 37,46,47 against angiogenesis, 48 as fluorescence tracers in cells, 49 against hepatitis B virus, 50 and nucleosides originally tested against adenosine deaminase, 51 hepatitis C virus, 52 and human cytomegalovirus. 53 We found that pyrazolo [3,4-c]pyridine, is a novel heterocyclic ring that bind ARs having antagonistic activity to A1R and A3R with potential for further development. We investigated experimentally for the identified two classes of pyrazolo [3,4-c]pyridines their (a) pharmacological profile using functional assays, (b) binding interactions and binding kinetic profile using, correspondingly, molecular dynamics (MD) simulations and mutagenesis experiments, and competition binding experiments with the NanoBRET 20 (Nano Bioluminescence resonance energy transfer) method.…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole and its derivatives have been widely applied in drug synthesis and biological activity 12 . Benzimidazole is used as an intermediate for many essential drug molecules, including omeprazole, 13 cyclobendazole, 14 maribavir, 15 etc. Generally, benzimidazole and its derivatives are synthesized by reacting o ‐phenylenediamine with carboxylic acids, esters and aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable organic molecules widely utilized as electro-, thermo-, and photo-sensitive building blocks in numerous materials are 4,4 -bipyridine derivatives, known as viologens [22]. The viologens have excellent redox ability and can act as suitable electron acceptors because of Lewis acidity and πdeficiency to form charge-transfer (CT) complexes with electron-rich species [23].…”
Section: Introductionmentioning
confidence: 99%